RELATIONSHIP BETWEEN SELF EFFICACY WITH CAREER MATURITY AT THE END COLLEGE STUDENTS - Lestari, Wigati Tri (EMPATHY Jurnal Fakultas Psikologi, 2013)
Abstract This research has purposed to understand correlation between self efficacy and the career maturity for final grade college students of university. This research includes 135 college students who was sitting at the end of the semeter of Accounting Course Economics Faculty in Ahmad Dahlan University. Instruments collecting data in this research using the scale. Items scale a statement favourable and unfavourable. There are two types of scales that are used as the data collection instrument self efficacy scale and career maturity scale. Method of analysis used correlation techniques product moment pearson. Over all data were processed with SPSS 17.0 for windows. The result of data analysis showed self efficacy scale has a reliability of 0,938 and career maturity scale has a reliability of 0,917. Based on correlation of test results is 0,346 at significance level 0,01. The results show the contribution of self efficacy variables to career maturity is equel 11,97%. The results of the test showed that was a significan positive relationship between self efficacy to career maturity at the end of the college students. Key Word: self efficacy, career maturity, the end college student.